A basic course in statistics with sociological applications - Anderson, Theodore R (Holt, Rinehart and Winston, 1975)
First ed. by Morris Zelditch, Jr., published in 1959 under title: A basic course in sociological statistics; Bibliography: p. 348-351; Neal A. Newfield, Ph.D., LICSW (Giver)